Development of an intelligent and remote IoT-based monitoring system for power quality application - Mohd Noh, Faridah Hanim; Zambri, Nor Aira; Ab.Rahman, Munirah; Ilomam, Mariyam Jamilah (Penerbit UTHM, 2020)
Power quality is an extremely critical when it comes to electricity consumer in all aspect of practices. A small variation in the voltage results in the shutdown of sensitive equipment and a brief shut down leads to additional production or operational cost. In order to solve the power quality issue, it is important to understand the characteristic of the power quality disturbance signal. A decent and efficient monitoring devise is essential to capture and analyze the disturbance signal. This project proposed a development of a remote intelligent IoT-based power quality monitoring device that able to monitor, capture, characterize, and diagnose the power quality event occured in the smart grid system or any electric distribution system based on Space Vector Machine Platform. It is expected that the proposed project will assist engineers to understand the power quality root caused effectively and able to react fast to mitigate the issue.